An alternative suggestion for the Pliocene onset of major northern hemisphere glaciation based on the geochemical provenance of North Atlantic Ocean ice-rafted debris - Bailey, Ian; Hole, Georgia M.; Foster, Gavin L.; Wilson, Paul A.; Storey, Craig; Trueman, Clive N.; Raymo, Maureen E. (Quaternary Science Reviews, 2013)
The onset of abundant ice-rafted debris (IRD) deposition in the Nordic Seas and subpolar North Atlantic Ocean 2.72 millions of years ago (Ma) is thought to record the Pliocene onset of major northern hemisphere glaciation (NHG) due to a synchronous advance of North American Laurentide, Scandinavian and Greenland ice-sheets to their marine calving margins during marine isotope stage (MIS) G6. Numerous marine and terrestrial records from the Nordic Seas region indicate that extensive ice sheets on Greenland and Scandinavia increased IRD inputs to these seas from 2.72 Ma. The timing of ice-sheet expansion on North America as tracked by IRD deposition in the subpolar North Atlantic Ocean, however, is less clear because both Europe and North America are potential sources for icebergs in this region. Moreover, cosmogenic-dating of terrestrial tills on North America indicate that the Laurentide Ice Sheet did not extend to ∼39°N until 2.4 ± 0.14 Ma, at least 180 ka after the onset of major IRD deposition at 2.72 Ma. To address this problem, we present the first detailed analysis of the geochemical provenance of individual sand-sized IRD deposited in the subpolar North Atlantic Ocean between MIS G6 and 100 (∼2.72–2.52 Ma). IRD provenance is assessed using laser ablation lead (Pb) isotope analyses of single ice-rafted (>150 μm) feldspar grains. To track when an ice-rafting setting consistent with major NHG first occurred in the North Atlantic Ocean during the Pliocene intensification of NHG (iNHG), we investigate when the Pb-isotope composition (206Pb/204Pb, 207Pb/204Pb, 208Pb/204Pb) of feldspars deposited at DSDP Site 611 first resembles that determined for IRD deposited at this site during MIS 100 (2.52 Ma), the oldest glacial for which there exists convincing evidence for widespread glaciation of North America. Whilst Quaternary-magnitude IRD fluxes exist at Site 611 during glacials from 2.72 Ma, we find that the provenance of this IRD is not constant. Instead, we find that the Pb-isotope composition of IRD at our study site is not consistent with major NHG until MIS G2 (2.64 Ma). We hypothesise that IRD deposition in the North Atlantic Ocean prior to MIS G2 was dominated by iceberg calving from Greenland and Scandinavia. We further suggest that the grounding line of continental ice on Northeast America may not have extended onto the continental shelf and calved significant numbers of icebergs to the North Atlantic Ocean during glacials until 2.64 Ma.